Pendred syndrome--100 years of underascertainment? - Reardon, W; Coffey, R; Phelps, P; Luxon, L; Stephens, D; Kendall-Taylor, P; Britton, K; Grossman, A; Trembath, R (1997)
Pendred syndrome is an autosomal recessive condition classically characterized by deafness and goitre. Since both cochlear and thyroid pathology are required to secure the diagnosis, it is unclear whether the condition might present without the classical features. The perchlorate discharge test, the gold-standard investigation for Pendred syndrome, is non-specific, and in the absence of alternative means of confirming the diagnosis, its sensitivity is unknown. We used the recent mapping of the gene to chromosome 7q to identify pedigrees with a likely diagnosis of Pendred syndrome, and assessed the prevalence of clinical parameters of disease in affected patients. Thirty-six familial cases showed co-segregation between disease and the Pendred syndrome locus on chromosome 7q. Clinical and investigative findings were compared in index cases (n = 18) vs. affected siblings (n = 18). The overall prevalence of goitre was 73%, higher in index cases (94%) than in siblings (56%), many of whom had not previously been considered to have the condition. One perchlorate discharge test was false-negative (2.9%). Radiological malformations of the cochlea were identified in 86% of cases. Securing a diagnosis of Pendred syndrome may be difficult, especially in the single case. The perchlorate discharge test, although valuable, is difficult to undertake in the younger patient, and radiology may assist in diagnosing such patients.